PENGEMBANGAN BAHAN AJAR AL-QUR’AN HADIST BERBASIS POWERPOINT DALAM MENINGKATKAN EFEKTIVITAS PEMBELAJARAN DI MTS SWASTA NURUL ISLAM KEUREUSEK - Khairuni, Azni (Journal of Contemporary Indonesian Islam, 2025)
This research aims to evaluate the effectiveness of using PowerPoint-based Al-Qur'an hadith teaching materials in the learning process at Nurul Islam Keureusek Private MTs. Based on the results of initial observations, it was found that the conventional teaching methods that have been used so far are less able to increase students' effectiveness and learning outcomes, students' low interest, participation and understanding of the material is the main reason for the need to develop more interesting teaching materials. To overcome this problem, researchers developed digital teaching materials using Microsoft PowerPoint which is designed interactively, equipped with supporting elements such as images, text, sound, video and animation to attract attention and facilitate students' understanding of the subject matter. This research uses the Research and Development (R&D) method with the ADDIE development model, which consists of Analysis, Design, Development, Implementation and Evaluation stages. The research results show that this PowerPoint-based teaching material is very effective in increasing learning motivation, students' active contribution during learning, and students' understanding of Al-Qur'an hadith material. Teaching materials have also been proven to make it easier for educators to convey material in a systematic way and in accordance with the Completion Criteria for Learning Objectives (KKTP). Thus, interactive PowerPoint can be used as an innovative and applicable solution to improve the quality of learning in madrasas.